A Comparative Analysis Of Improvisational Techniques In Jazz And Pop Piano Performance - Bagamanova Adilya Talkhaevna (Genius Journals, 2025)
This article presents a comparative analysis of improvisational techniques in jazz and pop piano performance. Drawing upon both domestic and international sources, the study explores the similarities and differences in approaches to improvisation, focusing on stylistic, modal, rhythmic, and textural aspects. Special attention is given to the development of improvisational skills among students of music conservatories and universities. The research confirms that jazz and pop improvisation foster different models of musical thinking, despite their superficial stylistic resemblance.
Keywords: improvisation; jazz; pop music; piano